Radiation Dose Optimization: Range Configuration on Computed Tomography Scans of Non-Contrast Head Scans with Hemiparese Cases - Verina, Alya; Pradika, Fannisa Rahma; Rahardian, Arga Pratama; Setialam, Farid (UM Purwokerto Press, 2025)
Approximately 80% of stroke patients experience weakness/hemiparesis on one side of the body due to vascular abnormalities in certain hemispheres. If hemiparese is not treated immediately, it can cause permanent disability. Supporting examination that can be used to diagnose hemiparese is a non-contrast head CT scan. There are several ranges that can be applied to the examination. This affects the dose received by the patient. This study aims to compare the radiation dose (CTDIvol and DLP) in non-contrast head CT scan examination in hemiparese cases between the range from vertex to sinus maxillaris and the range from vertex to basic cranii. The research was conducted at KRT Setjonegoro Wonosobo Hospital in December 2023 using quantitative method. Data were obtained from a non-contrast head CT scan examination with hemiparese cases using the range vertex to sinus maxillary and range vertex to basic crani. Results: In the head CT Scan examination of hemiparese cases, the CTDIvol value for the range Vertex to sinus maxillaris and the range Vertex to basic cranii is 45.5 ± 12.6 mGy and 48.8 ± 14.6 mGy, while for the DLP for the range Vertex to sinus maxillaris is 609.8 ± 47.9 mGy.cm and for the range Vertex to basic cranii is 878.9 ± 42.1 mGy.cm. CTDIvol value is found to have no significant difference, but for the DPL value there is a significant difference in the non-contrast head CT scan examination without contrast with hemiparese cases The 2 CTDIvol and DLP values are still in accordance with the DRL recommendations recommended by Nuclear Energy Regulatory Agency (BAPETEN).